2009
DOI: 10.1186/1472-6807-9-16
|View full text |Cite
|
Sign up to set email alerts
|

Rational mutagenesis to support structure-based drug design: MAPKAP kinase 2 as a case study

Abstract: Background: Structure-based drug design (SBDD) can provide valuable guidance to drug discovery programs. Robust construct design and expression, protein purification and characterization, protein crystallization, and high-resolution diffraction are all needed for rapid, iterative inhibitor design. We describe here robust methods to support SBDD on an oral anti-cytokine drug target, human MAPKAP kinase 2 (MK2). Our goal was to obtain useful diffraction data with a large number of chemically diverse lead compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Deletion of the activation loop was not tolerated, while the overall crystallization process was more sensitive to N -truncation in comparison to C -truncation. 33 Another study showed that deletion of the 1-40 sequence of the Pro-rich domain resulted in higher expression level and enhanced solubility of MK2, while best crystals were built upon removing part of the C terminal domain (namely, the sequence 365-400). 35 The constitutively active form 41-364 of MK2 was thus crystallized with both ADP and the broad-spectrum kinase inhibitor staurosporine 152 (PDB entries 1ny3 and 1nxk, solved at 3.2 and 2.7 Å, respectively, Table 1).…”
Section: Crystallization Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Deletion of the activation loop was not tolerated, while the overall crystallization process was more sensitive to N -truncation in comparison to C -truncation. 33 Another study showed that deletion of the 1-40 sequence of the Pro-rich domain resulted in higher expression level and enhanced solubility of MK2, while best crystals were built upon removing part of the C terminal domain (namely, the sequence 365-400). 35 The constitutively active form 41-364 of MK2 was thus crystallized with both ADP and the broad-spectrum kinase inhibitor staurosporine 152 (PDB entries 1ny3 and 1nxk, solved at 3.2 and 2.7 Å, respectively, Table 1).…”
Section: Crystallization Studiesmentioning
confidence: 99%
“…X-ray crystallography studies reveal that MK2 can be arranged in trimer structures that are however unable to give interactions with p38. Seven different crystal forms of MK2 (referred to as rods, plates, cubes, bipyramids, hexagonal bullets, hexagonal bullets collapsed from the latter form, and sharp blocks) have been identified and described by different research groups . An analysis of the MK2 crystal structures deposited within the PDB reveals that the construct 41–364 (a constitutively active form of the enzyme) has been most often used to obtain complexes between the protein and various small molecule inhibitors (Table ).…”
Section: Crystallization Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Three-dimensional (3D) X-ray crystal structures of MK2 apoenzyme, truncated and point mutated forms, and of MK2 in complex with p38 MAPK , ADP, AMPPNP, or staurosporine have been published [ 57 , 63 65 ]. Recently, an X-ray structure of MK3 in complex with the pharmaceutical lead compound P4O was also published [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…TNF-is implicated in several inflammatory diseases such as rheumatoid arthritis, and therefore inhibition of TNFactivity represents a most promising target for anti-inflammatory therapy (Camussi & Lupia, 1998;Kotlyarov et al, 1999). Several groups have reported programs to develop antiinflammatory therapies through the generation of MK2 inhibitors and determined the crystal structure of MK2 (Wu et al, 2007;Hillig et al, 2007;Velcicky et al, 2010;Anderson et al, 2007Anderson et al, , 2009aRevesz et al, 2010;Argiriadi et al, 2009Argiriadi et al, , 2010Fujino et al, 2010;Barf et al, 2011). With the exception of two inhibitor complex structures, TEI-I01800 [Protein Data Bank (PDB) code 3a2c; Fujino et al, 2010] and 2,4-diaminopyrimidine derivative from Abott (PDB code 3ka0; Argiriadi et al, 2010), all MK2 complexes deposited in the PDB have asheet Gly-rich loop (-form).…”
Section: Introductionmentioning
confidence: 99%